2016
DOI: 10.1371/journal.pone.0145779
|View full text |Cite
|
Sign up to set email alerts
|

Design Characteristics Influence Performance of Clinical Prediction Rules in Validation: A Meta-Epidemiological Study

Abstract: BackgroundMany new clinical prediction rules are derived and validated. But the design and reporting quality of clinical prediction research has been less than optimal. We aimed to assess whether design characteristics of validation studies were associated with the overestimation of clinical prediction rules’ performance. We also aimed to evaluate whether validation studies clearly reported important methodological characteristics.MethodsElectronic databases were searched for systematic reviews of clinical pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
2
10
1
1
Order By: Relevance
“…This confirms that case-control studies should not be used to study certain aspects of model calibration. Further, we found that the total OE ratio was influenced by the method of outcome assessment, in agreement with previous studies that showed that higher diagnostic odds ratios were found in studies with differential outcome verification 13. We also expected to find lower OE ratios when the validation population differed from the development population (eg, in terms of case-mix) 14.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This confirms that case-control studies should not be used to study certain aspects of model calibration. Further, we found that the total OE ratio was influenced by the method of outcome assessment, in agreement with previous studies that showed that higher diagnostic odds ratios were found in studies with differential outcome verification 13. We also expected to find lower OE ratios when the validation population differed from the development population (eg, in terms of case-mix) 14.…”
Section: Discussionsupporting
confidence: 90%
“…We could not systematically confirm this across all reviews, likely caused by heterogeneity between systematic reviews as indicated by the wide confidence intervals. Finally, we could not fully confirm the association between sample size and model performance that was previously found,13 although we found similar trends in part of the reviews.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…This study has some important limitations. 33 One of the most important limitations is the performance of the study in the same cardiac surgery center. This could lead to the unknowing duplication of the same errors that may contribute to the development of delirium, and which will not occur in another center.…”
mentioning
confidence: 99%
“…This may help to understand under what circumstances the model performance remains adequate, and when the model might require further improvements. As mentioned earlier, the discrimination and calibration of a prediction model can be affected by differences in the design 38 and in populations across the validation studies, for example, owing to changes in case mix variation or baseline risk. 8 22 In general, sources of heterogeneity can be explored by performing a meta-regression analysis where the dependent variable is the (transformed) estimate of the model performance measure.…”
Section: Investigating Heterogeneity Across Studiesmentioning
confidence: 99%